2018
DOI: 10.1080/1350293x.2018.1442042
|View full text |Cite
|
Sign up to set email alerts
|

Parental involvement in Finnish day care – what do early childhood educators say?

Abstract: Research conducted in recent decades shows that parental involvement plays a significant role in the academic achievement and the healthy development of children. Gaining a better understanding of early childhood educators' views and the reasons for insufficient practices is important for improving parental involvement. This mixed-method research investigates the views on parental involvement held by early childhood educators in Finland. A representative sample of 287 educators from Helsinki completed a questi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 40 publications
0
14
0
2
Order By: Relevance
“…Karena sekolah tahu apa yang diinginkan orang tua untuk anaknya sehingga orang tua perlu terlibat pada programprogram sekolah yang dirancang. Lebih jauh, keterlibatan orang tua dalam pendidikan akan membantu anak lebih mudah dalam memahami pembelajaran yang diberikan oleh sekolah formal (Hakyemez-Paul et al, 2018).…”
Section: Pendahuluanunclassified
See 1 more Smart Citation
“…Karena sekolah tahu apa yang diinginkan orang tua untuk anaknya sehingga orang tua perlu terlibat pada programprogram sekolah yang dirancang. Lebih jauh, keterlibatan orang tua dalam pendidikan akan membantu anak lebih mudah dalam memahami pembelajaran yang diberikan oleh sekolah formal (Hakyemez-Paul et al, 2018).…”
Section: Pendahuluanunclassified
“…Pengambilan keputusan secara sepihak dilakukan ketika belajar beribadah, melakukan sesuatu yang membahayakan, dan berkaitan dengan aturan sekolah. Anak usia dini membutuhkan perhatian yang lebih banyak dibandingkan anak yang lebih tua (Hakyemez-Paul et al, 2018). Mereka masih membutuhkan pendampingan dan pengawasan ketika bermain.…”
Section: Kerjasama Orangtua Anak Dan Guruunclassified
“…113 early childhood educators who were employed at various ECE institutions in Ankara, the capital of Turkey, participated in this research in 2012, which was the first set of data collected from Turkey for this study. In the second article (Hakyemez-Paul et al, 2018a), early childhood educators' views on parental involvement and their parental involvement practices were investigated in the Finnish context, whereas in the third article (Hakyemez-Paul et al, 2018b) the focus was Finnish early childhood educators' self-reported reasons for insufficient parental involvement practices in their institution. For the second and third articles, the same data were used, which were gathered from early childhood educators working in Helsinki, the capital of Finland in 2015, including 287 participants (Hakyemez-Paul et al, 2018a;2018b).…”
Section: Structure Of the Dissertationmentioning
confidence: 99%
“…In the second article (Hakyemez-Paul et al, 2018a), early childhood educators' views on parental involvement and their parental involvement practices were investigated in the Finnish context, whereas in the third article (Hakyemez-Paul et al, 2018b) the focus was Finnish early childhood educators' self-reported reasons for insufficient parental involvement practices in their institution. For the second and third articles, the same data were used, which were gathered from early childhood educators working in Helsinki, the capital of Finland in 2015, including 287 participants (Hakyemez-Paul et al, 2018a;2018b). Finally, the fourth article (Hakyemez-Paul et al, under review), which adopted a comparative approach across the two countries, make use of the data collected in Finland in 2015 and a new dataset from Turkey.…”
Section: Structure Of the Dissertationmentioning
confidence: 99%
“…There is strong evidence that parent engagement in education during the early childhood years contributes to positive child outcomes and academic achievement, and parent engagement is considered as a key strategy for closing the achievement gap (Henderson et al 2004;Hepburn 2004;Vlasov and Hujala 2017). This literature explores various approaches to and/or benefits of parent involvement, and how parent engagement might influence children's academic learning (Hakyemez-Paul et al 2018;Morrow and Malin 2004;Park and McHugh 2014). Research across international contexts notes the importance of parent engagement and parent-teacher partnerships as a core element of quality ECE and one that merits further attention in both research and practice (OECD 2012(OECD , 2017Vlasov and Hujala 2017;Douglass 2011;Douglass and Klerman 2012).…”
Section: Literature Reviewmentioning
confidence: 99%